2017
DOI: 10.1371/journal.pone.0169184
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection Is Associated with Increased Fatty Infiltration of the Thigh Muscle with Aging Independent of Fat Distribution

Abstract: BackgroundLower muscle density on computed tomography (CT) provides a measure of fatty infiltration of muscle, an aspect of muscle quality that has been associated with metabolic abnormalities, weakness, decreased mobility, and increased fracture risk in older adults. We assessed the cross-sectional relationship between HIV serostatus, age, thigh muscle attenuation, and thigh muscle cross-sectional area (CSA).MethodsMean CT-quantified Hounsfield units (HU) of the thigh muscle bundle and CSA were evaluated in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…Several studies [7, 33, 34] have shown associations between less dense thigh musculature with poorer lower limb performance, which may contribute to mobility impairment. Although most prior studies of muscle density and area have focused on thigh musculature, Goodpaster et al observed that trunk muscle density (our primary outcome) was strongly correlated with thigh density (r=0.65–0.77; p<0.01) [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies [7, 33, 34] have shown associations between less dense thigh musculature with poorer lower limb performance, which may contribute to mobility impairment. Although most prior studies of muscle density and area have focused on thigh musculature, Goodpaster et al observed that trunk muscle density (our primary outcome) was strongly correlated with thigh density (r=0.65–0.77; p<0.01) [26].…”
Section: Discussionmentioning
confidence: 99%
“…PLWH with lipodystrophy had significantly lower median muscle density (55.0 HU; IQR 51.0–58.3) compared to PLWH without lipodystrophy (57.0 HU; IQR 55.0–59.0) and HIV-uninfected men (59.5 HU: IQR 57.3–64.8) [39]. In the Multicenter AIDS Cohort Study, men with HIV (~57 years old) on antiretroviral therapy had lower thigh muscle density (by 1 HU), compared to their HIV-uninfected peers (~54 years old), and lower thigh muscle density was correlated with greater VAT area and weaker grip strength [7]. We have previously shown that antiretroviral therapy initiation was associated with a decrease in trunk muscle density (−0.87 to −2.4 HU across muscle groups) over 96 weeks [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that ART initiation is associated with significant increases in skeletal muscle fat with minimal gains in skeletal muscle lean area [65] . In a cross-sectional study within the MACS, we found more skeletal muscle fat with increasing age among HIV-infected men, independent of body fat distribution, compared to HIV-uninfected men [66] . A small study of 40 community-dwelling HIV-infected individuals in Rochester, NY reported an association between impaired physical function and the ratio of intramuscular to total body fat [61] .…”
Section: Sarcopeniamentioning
confidence: 99%
“…Few studies have described the changes in skeletal muscle fat that occur with HIV infection; to the best of our knowledge, no studies have described changes in skeletal muscle fat with ART initiation. Compared to HIV-uninfected men, HIV-infected men had lower density (greater fatty infiltration) of the mid-thigh muscle bundle and lower muscle quality with age, even after multivariable adjustment including VAT and SAT [16]. Among younger HIV-infected persons with body fat changes (previously referred to as lipodystrophy), decreased psoas muscle density was more strongly associated with insulin resistance than BMI, subcutaneous fat, lean body mass, or ART [17].…”
Section: Introductionmentioning
confidence: 99%